Crystal structure of (E)-2-cyano-3-(12-methyl-12H-benzo[b]phenothiazin-11-yl)acrylic acid - Motonori Watanabe (Acta Crystallographica Section E, 2014)
In the title compound, C21H14N2O2S, a donor–acceptor type of benzo[b]phenothiazine (bpz) derivative, the thiazine ring adopts a boat conformation and the bond-angle sum at the N atom is 360.0°. The dihedral angle between the benzene ring and the naphthelene ring system fused to the thiazine ring is 32.76 (5)°. In the crystal, carboxylic-acid inversion dimers linked by pairs of O—H...O hydrogen bonds generate R22(8) loops. Aromatic π–π stacking [shortest centroid–centroid separaton = 3.5242 (13)Å] consolidates the structure and very weak C—H...O and C—H...N interactions also occur.